Prevalence, detection of virulence genes and antimicrobial susceptibility of Escherichia coli isolated from arbor acres broilers feeding cycle in China - Zhou, Qian; Tang, Mengjun; Zhang, Xiaoyan; Tang, Xiujun; Lu, Junxian; Gao, Yushi (Frontiers in Veterinary Science, 2024)
The prevalence of antimicrobial resistance originating from animals presents a significant threat to the treatment of animal disease, public health, and food safety. Researchers have focused on antibiotic resistance in Escherichia coli (E. coli), yet there are few reports on the resistance change during the feeding cycle. The purpose of this study was to investigate the prevalence and antibiotic resistance changes of E. coli in animal, environmental, and human samples during the broiler feeding cycle. Epidemiological surveys were performed in a farm with feeding AA broilers in Yangzhou, Jiangsu Province, China. Results showed that during a 42-days feeding cycle, 128 E. coli isolates were obtained from the cloaca of white-feathered broilers (n = 140), with an isolation rate of 91.4%, 27 E. coli isolates were obtained from Feed (n = 70) and 35 E. coli isolates were obtained from cage swabs (n = 70). A workers’ hands swabs sample isolation rate of 68.6% (24/35) was observed. Antibiotic susceptibility testing revealed that out of 214 E. coli isolates, varying degrees of resistance were observed against 14 antibiotics. Most strains were resistant to ampicillin, cephalothiophene, ciprofloxacin, tetracycline, sulfamisoxazole, sulfamethoxazole and florfenicol, with a resistance rate exceeding 80%. The resistant strains demonstrated relatively stable patterns in their resistance to various antibiotics. Of the six antibiotic resistance genes tested, the floR gene showed the highest detection rate (72.4%), followed by qnrS (43.0%), mcr-1 (35.0%), aadE-Sat4-aphA-3 (28.0%), blaNDM (8.4%), aac(6′)-lb (3.7%), and cfr (0). The highest detection rate for virulence genes was yijp. In summary, the isolation rate of E. coli and antibiotic resistance profile in broiler chickens remained stable throughout their feeding cycle. These findings can serve as a reference for the rational use of antibiotics in clinical settings, they can guide the use of veterinary drugs in poultry breeding.